Evaluation of Suicidal Symptoms in Adult Depressive In-Patients at Birat Medical College and Teaching Hospital - Upadhyay, Shikha; Shrestha, Sirshak Deep; Karki, Diksha; Koirala, Akshika; Paudel, Ajita (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Suicide is a critical public health concern and a leading cause of death globally, particularly among individuals with major depressive disorder (MDD). Understanding the prevalence and correlates of suicidal symptoms in hospitalized depressive patients is crucial for effective intervention and prevention strategies. This study aimed to evaluate the prevalence, severity, and associated factors of suicidal symptoms in adult depressive in-patients at Birat Medical College and Teaching Hospital, focusing on gender differences and clinical predictors. MATERIAL AND METHODS A descriptive, cross-sectional study was conducted over a 1-year period (July 2022 - June 2023). A total of 120 adult in-patients diagnosed with MDD according to DSM-5 criteria were selected using purposive sampling. Data were collected using a structured proforma and the Hamilton Depression Rating Scale (HDRS). Statistical analyses included descriptive statistics, independent t-tests, Spearman’s correlation, and regression analysis. RESULTS Of the 120 patients, 54% reported suicidal ideation, with a higher prevalence among females (68%) compared to males (44%). Signiﬁcant positive correlations were found between HDRS scores and suicidal symptoms (r = 0.74, p < 0.001). Regression analysis indicated that HDRS scores and duration of illness were signiﬁcant predictors of suicidal symptoms (R² = 0.68, p <0.01). CONCLUSION Suicidal symptoms are highly prevalent among depressive in-patients, especially in females. The severity of depression and longer duration of illness are associated with an increased risk of suicidal behavior. These ﬁndings highlight the importance of routine screening and targeted interventions in hospitalized patients with MDD.